The Usefulness of Financial Statement Information in Predicting Stock Returns: New Zealand Evidence - Jonathan Goslin; Daniel Chai; Abeyratna Gunasekarage (Australasian Accounting, Business and Finance Journal, 2012)
This study examines whether financial statement information can be used to implement an investment strategy in order to earn abnormal returns. Using financial statement information, we develop multiple logit models that predict either the year-ahead earnings changes (earnings-based approach) or the direction of stock returns (returns-based approach). The study labels the earnings-based approach as the ‘indirect method’ and the returns-based approach as the ‘direct method’. The coefficient estimates of these models are used to generate Pr measures which are used to formulate investment strategies. Specifically, an investment strategy that involves buying stocks with high Pr values and selling stocks with low Pr values is examined. We find that both approaches generate positive returns for holding periods between six to eighteen months. However, when the influence of stock characteristics was analysed, only the Pr measures generated by the direct method demonstrated a significant influence on the stock returns. These findings remained unchanged across a number of sensitivity tests conducted.
Keywords: Financial statement information; Logit Models; New Zealand market